What are the Sources of Leader Charisma? An Inductive Study from China - Yangfeng Cao; Kai Zhang; Wenhao Luo (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2013)
This study aims to put forward a new concept in charismatic leadership theory: source of leader charisma (SLC). Using an inductive approach, we identified the various dimensions of SLC in the Chinese context, and found that SLC comprises of charismatic personality and charismatic behaviors. Charismatic personality consists of three dimensions: high morality, outstanding talents, and attractive characteristics. Charismatic behavior also includes three dimensions: visional inspiration, character development, and morale stimulation. Finally, we developed a primary model to explore the mechanism by which the SLCs are attributed to charisma by follower. Our findings in the present study contribute to new evidence that charismatic leadership theory may transcend cultural boundaries.
hdl:10398/8659
Keywords: 330; Leadership theory; Charismatic leadership; China; Source of leader charisma; Führungspersönlichkeit; China